Превентивний контроль Конституційного Суду України щодо внесення змін до Основного Закону держави - Рудик, Петро Андрійович (My University, 2014)
У статті вперше комплексно досліджується проблема превентивного контролю Конституційним Судом України шодо внесення змін до Основного Закону держави. The article reveals the problem of complex preventive control by the Constitutional Court of Ukraine regarding to making amendments to the Basic Law of the State for the first time.
Keywords: превентивний конституційний контроль; внесення змін; Конституція України; the procedure for making amendments; Constitution of Ukraine; preventive constitutional review; кафедра економіки і права